Thermal proteome profiling reveals Haemonchus orphan protein HCO_011565 as a target of the nematocidal small molecule UMW-868 - Taki, Aya C.; Wang, Tao; Nguyen, Nghi N.; Ang, Ching-Seng; Leeming, Michael G.; Nie, Shuai; Byrne, Joseph J.; Young, Neil D.; Zheng, Yuanting; Ma, Guangxu; Korhonen, Pasi K.; Koehler, Anson V.; et al. (Frontiers in Pharmacology, 2022)
Parasitic roundworms (nematodes) cause destructive diseases, and immense suffering in humans and other animals around the world. The control of these parasites relies heavily on anthelmintic therapy, but treatment failures and resistance to these drugs are widespread. As efforts to develop vaccines against parasitic nematodes have been largely unsuccessful, there is an increased focus on discovering new anthelmintic entities to combat drug resistant worms. Here, we employed thermal proteome profiling (TPP) to explore hit pharmacology and to support optimisation of a hit compound (UMW-868), identified in a high-throughput whole-worm, phenotypic screen. Using advanced structural prediction and docking tools, we discovered an entirely novel, parasite-specific target (HCO_011565) of this anthelmintic small molecule in the highly pathogenic, blood-feeding barber’s pole worm, and in other socioeconomically important parasitic nematodes. The “hit-to-target” workflow constructed here provides a unique prospect of accelerating the simultaneous discovery of novel anthelmintics and associated parasite-specific targets.